In Search of A Just And Equitable Agricultural Land Dispute Settlement In Indonesia - Prasanthi, Antarin; Daryono, Daryono (Brawijaya Law Journal, 2023)
Agricultural land dispute is commonly resolved by a non-judicial settlement. It however experienced silent conflict and a just and due process of law due to multiple interests involved. Responding to these salient disputes, in 2021 the International Institute for Unification of Private Law (UNIDROIT) established a legal guide to assist developing countries to draft a more sustainable and responsible agricultural land investment contract (ALIC). In Liew to the UN Guiding Principle on Business and Human Rights (2011), the state and enterprises shall exercise adequate oversight to protect the breach of human rights including the customary land rights. The research aims at assessing the agricultural land dispute settlement pursuant to ALIC. It was found that land dispute settlement was dependent upon the maintenance of social control consisting of a dynamic mixture of informal and formal systems. This type of social control enabled creating a balance between disputants, minimizing transactional costs and promoting effective law enforcement. The article elaborated land dispute settlement in two different cases in Indonesia and discusses non-litigation hybrid model of land dispute resolution to promote a better strategy for resolving a land dispute in Indonesia. At the same time, this model may serve as a potential method to provide a better strategy to promote private rulemaking to prevent further disputes as a transition to the application of ALIC.